ASAL PENCIPTAAN PEREMPUAN - Basid, Abdul (UNIVERSUM : Jurnal KeIslaman dan Kebudayaan, 2017)
Polemic on the origin of women creation is still exist, since the study on misoginis hadith on those problem is still interesting to be discuss. This article tries to reveal the origin of women creation focusing on text analysis through takhrÃ„Â«j al-Ã¡Â¸Â¥adÃ„Â«th method in Bukhori and Muslim books. Hadith texts stating that the origin of women is created from menÃ¢â‚¬â„¢s rib based on feminism movement is considered invalid, although it comes from Ã¡Â¹Â£Ã„ÂÃ¡Â¸Â¥iÃ¡Â¸Â¥ain book since it gives negative impression toward women position. Those negative impression can be lost when the meaning toward those hadith through metaphor, not through textual meaning. Keywords: creation, women, Takhrij al-Ã¡Â¸Â¤adÃ„Â«th.